TEKNOLOGI DAN HIDUP KUDUS: Bagaimana Generasi Z Mengintegrasikan Nilai-Nilai Kristen Dalam Era Digital - Risdayana Rudding; Melda Melda; Femi Yanti Ramme; Delly Itania Ruben; Sriweni Antika Masarrang (TARBIYATUL ILMU: Jurnal Kajian Pendidikan, 2023)
This research investigates the complexity of the relationship between digital technology and the understanding and application of Christian values in the lives of Generation Z. As a generation growing up in the digital era, Generation Z faces unique challenges in integrating religious values with the increasingly pervasive use of technology in their daily lives. The study explores the impact of technology on how Generation Z interacts with Christian values, as well as the efforts and strategies they employ to live a holy life in the digital realm. The research methodology includes surveys and online content analysis to comprehend the behavioral patterns, attitudes, and experiences of Generation Z in integrating Christian values in the digital era. The findings indicate that despite facing temptations from online content conflicting with Christian teachings, Generation Z also utilizes technology to deepen their spiritual beliefs. Churches and religious communities play a central role in providing support, ethical guidance in the digital realm, and community spaces to help Generation Z navigate moral dilemmas in the digital world. The implications of the research underscore the need for a holistic approach from churches and religious communities to support Generation Z in living a holy life amidst the rapid development of technology.